Experimenting with education: spaces of freedom and alternative schooling in the 1970s. Issue 2 (30th September 2014) - Julie McLeod, Professor; McLeod, Julie
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore philosophies of progressive education circulating in Australia in the period immediately following the expansion of secondary schools in the 1960s. It examines the rise of the alternative and community school movement of the 1970s, focusing on initiatives within the Victorian government school sector. It aims to better understand the realisation of progressive education in the design and spatial arrangements of schools, with specific reference to the re-making of school and community relations and new norms of the student-subject of alternative schooling. Design/methodology/approach – It combines historical analysis of educational ideas and reforms, focusing largely on the ideas of practitioners and networks of educators, and is guided by an interest in the importance of school space and place in mediating educational change and aspirations. It draws on published writings and reports from teachers and commentators in the 1970s, publications from the Victorian Department of Education, media discussions, internal and published documentation on specific schools and oral history interviews with former teachers and principals who worked at alternative schools. Findings – It shows the different realisation of radical aims in the set up of two schools, against a backdrop of wider innovations in state education, looking specifically at the imagined effects of re-arranging the physical and symbolic space of schooling. Originality/value – Its value lies in offering the beginnings of a history of 1970s educational progressivism. It brings forward a focus on the spatial dimensions of radical schooling, and moves from characterisation of a mood of change to illuminate the complexities of these ideas in the contrasting ambitions and design of two signature community schools.